1H NMR-based metabonomics of the protective effect of Curcuma longa and curcumin on cinnabar-induced hepatotoxicity and nephrotoxicity in rats. (August 2015) - Wang, Haifeng; Su, Guangyue; Chen, Gang; Bai, Jiao; Pei, Yuehu
Highlights: Investigate protective effects of Curcuma longa and curcumin on heavy-metal toxicities. Curcuma longa and curcumin have the effective protection function through regulating the energy metabolism. Curcuma longa and curcumin have the effect to balance gut bacteria metabolism. Curcuma longa and curcumin have the effect to regulate the action of amino acid metabolism disturbance. Abstract: Curcuma longa is a perennial herb that is widely cultivated extensively in Asia and Africa. Curcumin is a major constituent of C. longa . A metabonomics approach based on high-resolution 1 H nuclear magnetic resonance spectroscopy was applied to investigate the toxicity protective effects of C. longa and curcumin in rats under cinnabar induced hepatotoxicity and nephrotoxicity. Partial least squares-discriminant analysis (PLS-DA) was performed to identify different metabolic profiles of urine and serum from rats. Liver and kidney histopathology examinations and serum clinical chemistry analysis were also performed. The significant difference in metabolic profiling of urine and serum of the rats was observed among cinnabar treated group, control group, co administration of C. longa and cinnabar, co administration of curcumin and cinnabar group. The results suggested that C. longa and curcumin have the effective protection function through regulating the energy metabolism, intestinal microflora and amino acid metabolism to the liver and kidney injury induced by cinnabar.